166k views
0 votes
Simplify the expression, show your work

Simplify the expression, show your work-example-1

1 Answer

2 votes

Answer:


(-y(2x^2 + y))/(x(6x - 5y^2))

Explanation:


((1)/(x^2)+(2)/(y))/((5)/(x)-(6)/(y^2)) =

To eliminate the denominators of the main numerator and denominator, we multiply the numerator and denominator of the main fraction by the LCD of all small denominators.

The LCD of x^2, y, x, and y^2 is x^2y^2.


= (x^2y^2 * ((1)/(x^2)+(2)/(y)))/(x^2y^2 * ((5)/(x)-(6)/(y^2)))


= (y^2 + 2x^2y)/(5xy^2 - 6x^2)


= (y(y + 2x^2))/(x(5y^2 - 6x))


= (-y(2x^2 + y))/(x(6x - 5y^2))

User Questionersam
by
5.6k points